A Case Study Of Great Eastern Life Assurance (M) Berhad - Lee, Hwee Hsiung (2007)
This research focuses on one of the most promising department of Great Eastern Life Assurance - the Group Insurance Department that offers products and services capable to grow in-tandem with the SME market. The feasibility study is to furnish additional information to assist the setup and refinement of its vision, mission and objective.